Kajian Efektifitas Kerja Operator dan Kondisi Alat pada Front Penambangan Tambang Besar Pemali PT Timah Tbk - Rajesta F. Wardana; E.P.S.B. Taman Tono; Delita Ega Andini (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2021)
The work efficiency value on the TB Pemali mining front in 2018 is relatively low (57.16%), This condition means it required the improvement of the work efficiency in accordance with the good mining practice. Method used in this research including preparation, collecting data and field orientation, which is then processed as follows: counting work efficiency of the dig tools for load and hauling tools in mining area front, analyzing operator performance and equipments conditions in mining area front, and analyzing work efficiency improvements. The result showing that score of current work efficiency of the dig tools for load in the amount of 62.74%, and for hauling tools in the amount of 57.68%. This result shows that low score of work efficiency in mining area front caused by large breakdown time of the hauling tools and low performance of the operator, then improvement of work efficiency is carried out by reducing the operator's variable trouble limit by 35% and reducing indent time of broke sparepart, the final score of work efficiency of the dig tools for load in mining area front is in the amount of 66.27% and for hauling tools in the amount of 66.44%